2021
DOI: 10.1200/op.20.01047
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prophylaxis With Biosimilar Filgrastim for Patients at Intermediate Risk for Febrile Neutropenia: A Cost-Effectiveness Analysis

Abstract: PURPOSE: Temporary COVID-19 guideline recommendations have recently been issued to expand the use of colony-stimulating factors in patients with cancer with intermediate to high risk for febrile neutropenia (FN). We evaluated the cost-effectiveness of primary prophylaxis (PP) with biosimilar filgrastim-sndz in patients with intermediate risk of FN compared with secondary prophylaxis (SP) over three different cancer types. METHODS: A Markov decision analytic model was constructed from the US payer perspective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
2
22
1
Order By: Relevance
“…Evidence shows that using biosimilar G-CSFs for primary prophylaxis among patients with intermediate risk can be a cost-effective strategy even without risk factors. 31 , 32 , 33 Moreover, short-term guidance issued by NCCN also states that prophylactic G-CSF use among patients receiving intermediate-risk regimens may be considered in the context of the COVID-19 pandemic. 34 New evidence and guidelines highlight the need for future studies focusing on this patient subgroup to inform clinical and reimbursement decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that using biosimilar G-CSFs for primary prophylaxis among patients with intermediate risk can be a cost-effective strategy even without risk factors. 31 , 32 , 33 Moreover, short-term guidance issued by NCCN also states that prophylactic G-CSF use among patients receiving intermediate-risk regimens may be considered in the context of the COVID-19 pandemic. 34 New evidence and guidelines highlight the need for future studies focusing on this patient subgroup to inform clinical and reimbursement decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the availability of biosimilar G-CSF agents, primary prophylaxis with G-CSF may be less cost-effective for FN prevention in breast cancer, when compared to secondary prophylaxis [ 21 ]. However, a recent cost-effectiveness analysis of biosimilar filgrastim found primary prophylaxis to be cost-effective and supported expanding the use of G-CSF as an effective method of reducing unnecessary healthcare facility visits, especially in the context of the COVID-19 pandemic [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous studies have suggested that the most cost-efficient approach to reducing the incidence of FN in chemotherapy-treated patients is through use of biosimilars and that savings could be used to expand access or reallocated to other anti-neoplastic therapy options on a budget-neutral basis [ 26 , 27 ]. Significant cost savings and increased access could potentially be realized for health systems that prioritize the use of biosimilars [ 22 ]. Nevertheless, the association between biosimilars and trends in G-CSF use in the Canadian context remains unclear and can be a compelling issue for additional investigation, including the extent to which FN-related hospitalizations have been impacted due to increased utilization of G-CSF prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…33 An analysis of biosimilar filgrastim for primary prophylaxis in patients receiving intermediate-risk, curative chemotherapy regimens for BC, non-small cell lung cancer, and non-Hodgkin lymphoma found it was costeffective compared to secondary prophylaxis. 34 Biosimilar access will be important to the health-care system, as the full benefits and savings biosimilars may provide will only be realized with continued growth in uptake and utilization. The economic implications of pegfilgrastim and biosimilar administration should be investigated in future health economics and outcomes research evaluating biosimilar versus reference products and including a cost component.…”
Section: Discussionmentioning
confidence: 99%